Beyond boundaries : the new neuroscience of connecting brains with machines-- and how it will change our lives - Nicolelis, Miguel A. L. (Times Books, 2011)
Draws on ground-breaking brain research to assess the potential of thought-controlled machines, which may enable significant technological advances in areas ranging from health care and manufacturing to global communication and space exploration.